Modeling and experimental validation of watertemperature in a fish rearing tank - Sarkar, Bikash; Tiwari, G N; Ayyappan, S (Indian Journal of Fisheries, 2014)
This study describes the modeling of a fish rearing tank. Numerical computationshave been performed for a typical day in the month of January, 2005 for thecomposite climate of New Delhi. This model has been developed by consideringthe effect of heat losses e.g. conduction, convection, radiation and evaporation.The governing equations are numerically solved with Matlab-7.0 software topredict the water temperature. The model has been validated with theexperimental data. It is inferred that the predicted and experimental values ofwater temperature exhibited fair agreement with coefficient of correlation(r = 0.90) and root mean square percent deviation is (e = 1.67%).